APPLICATION OF ICT IN PROFESSIONAL TRAINING OF JUNIOR MEDICAL STAFF IN THE PROCESS OF PROFESSIONAL DISCIPLINES OF PSYCHIATRIC PROFILE - Iliasova Y. (Kherson State University, 2018)
In the article the definition «information and communication technologies» (ICT) is analyzed. The advantages and disadvantages of using ICT in the professional training of future medical junior staff have been highlighted. It has been stressed about the importance and necessity of introduction of ICT in Ukrainian medical education. The concept of "mental maps" is analyzed. The article shows real interactive using of the service LearningApps and mental maps in the process of professional training of future junior medical staff during in the study of professional disciplines. The article discusses features of organization and holding of control lessons for students in Vinnytsia medical college, including professional disciplines «Psychiatry and narcology», «Nursing in psychiatry and narcology», «Neurology and psychiatry». The author formulated methods, which includes a control test, game exercises, practical skills and situational tasks created in the Web service LearningApps. The technique of conducting of control lesson is outlined, where students work on an interactive whiteboard. The structure of the control lesson is made in the form of a modern innovative tool - mental map was demonstrated. It is emphasized that this technique, will increase the quality of professional training of future junior medical staff. It is concluded that information and communication technologies (ICT) are the main tools for modernizing medical education and economic growth of our society.